SISTEM PENUNJANG KEPUTUSAN DALAM MENENTUKAN INSENTIF BAGI KARYAWAN MENGGUNAKAN METODE PROMETHEE - Aorora Mahardika, Sri Siswanti, Tri Irawati (Jurnal Ilmiah SINUS, 2017)
PT. Sami Surya Indah has 7,100 employees who provide incentive issues, in addition to the current handling of obstacles in reporting and determination of employees who deserve incentives. The current system in the Company is still using manual process where the database used is still in paper form. For that will be designed and made a decision support system to determine the incentives for employees with the method Promethee in PT. Sami Surya Indah. The purpose of this study is to design and build systems that can assist in determining the feasibility of providing incentives to prospective employees. This study also aims to apply the Promethee method for determining the feasibility of providing incentives to employees. Methods of data collection include field study and literature study. Field studies include interviews and observations. While the literature study conducted by examining the relevant literature with the problem. Designing system design using CD (Context Diagram), DFD (Data Flow Diagram) and ERD (Entity Relation Diagram), Implementation program with PHP and database MySql. The results of the functionality test shows the application is running in accordance with its function and based on the validity test of the application has been declared valid. In performing system performance testing the author uses Blackbox method. Keywords: Decision Support System, Promethee Method, Incentive Determination